Football Investment and Economic Diversification in Islamic Economies: Evidence from GCC Countries - Mohamed Abou Elseoud; Mohamed Yassin (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2026)
This study examines the effect of football investment on economic diversification in GCC countries during the period 2000–2024. The analysis focuses on whether football-related investment contributes to non-oil economic growth, tourism expansion, and infrastructure development. This issue has become increasingly important as GCC economies continue to pursue long-term diversification strategies aimed at reducing dependence on oil revenues. The previous literature focuses on the short-term effects of mega sporting events, while this study examines both short-term and long-term economic effects of continuous football investment. The study employs a quantitative econometric framework using panel data analysis, Fixed Effects estimation, Difference-in-Differences, and the Synthetic Control Method. The results reveal that football investment has a positive and statistically significant effect on non-oil GDP growth, tourism activity, and infrastructure development across GCC countries. Major football events also generate substantial short-term economic gains, particularly in tourism, construction, and service sectors, while several positive effects continue beyond the event period. The paper concludes that football investment can support broader economic transformation when integrated into long-term development strategies, effective governance frameworks, and tourism-oriented policies. The paper contributes to sports economics and economic diversification literature by providing long-term empirical evidence from GCC economies and offering practical policy insights for sustainable development strategies